The Effect of Boron Doping Concentration on the Electrochemical Oxidation of Chlorine Using BDD Electrode. Issue 3 (1st March 2023) - Li, Zhishen; Zhou, Bo; Yang, Wanlin; Deng, Zejun; Chen, Fenglei; Bai, Hena; Sharel, P. E.; Ma, Li; Wei, Quiping; Long, Hangyu
Abstract : Boron-doped diamond (BDD) electrode is an excellent candidate for anodic electrochemical oxidation of wastewater. However, higher concentrations of ClO3 − and ClO4 − of biotoxicity was found during chloride electrolysis using BDD electrodes compared to other electrode materials. In this study, BDD electrodes with five different boron doping concentrations were fabricated on silicon substrates using hot-filament chemical vapor deposition (HFCVD) method. The physical and electrochemical characterisation were conducted, which confirmed that with the decrease of boron concentration, the crystal size of the diamond decreased, oxygen evolution potential decreased, charge transfer resistance decreased while the electro-active surface area (EASA) increased. The electrochemical oxidation experiments of NaCl solution were carried out with these five BDD electrodes and time-dependent traces of product concentrations, current efficiencies and energy consumptions were compared and discussed. When the boron concentration increased, the minimum energy required to produce unit active chlorine (AC) decreased initially then increased, the same tendency was found in the yields of ClO3 − and ClO4 − . The lightly doped BDD (1.23 × 10 20 cm −3 ) showed low energy consumption and high yield of AC, and low yields of ClO3 − and ClO4 − . Electrolysis of chlorine-containing organic wastewater was studied which further demonstrated the good performance of lightly doped BDD electrode.